Oral health of smokers and e-cigarette users: a case-control study - Ghazali, Aini Fatimah; Ismail, Ahmad Faisal; Faisal, Ghasak Ghazi; Muhamad Halil, Mohd Haikal; Daud, Azlina (Ectodermal Displazi Grubu, 2018)
The objective of this study was to evaluate and compare the oral health of cigarette smokers, e-cigarette smokers, and non-smokers. This observational study involved 120 participants; 40 each in the control, cigarette, and e-cigarette groups respectively. Oral health examination was conducted according to the World Health Organization (WHO) criteria. Dental caries was evaluated using the DMFT index, while the periodontal parameters assessed using plaque, gingivitis, gingival bleeding, and calculus indices. The results from the 3 groups were compared using analysis of variance (MANOVA), the outcomes of which were significant for the Gingival Index (p = 0.000), Plaque Index (p = 0.012), and Bleeding Index (p = 0.001) of periodontal health. Post-hoc tests with Bonferroni correction revealed significant differences in the Gingival Index between the control and cigarette groups (p = 0.001), as well as cigarette and e-cigarette groups (p = 0.000). Meanwhile, Bleeding Index was only significantly different between the control and e-cigarette groups (p = 0.001). For Plaque Index, significant differences were seen between the control and cigarette groups (p = 0.016). There were no significant differences in the other periodontal health parameters, as the p values of the Calculus Index and DMFT Index were 0.955 and 0.702 respectively. In conclusion, e-cigarettes had potentially detrimental effects on oral health.